The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1177/0042085914536997
|View full text |Cite
|
Sign up to set email alerts
|

Does Biliteracy + Mathematical Discourse = Binumerate Development? Language Use in a Middle School Dual-Language Mathematics Classroom

Abstract: Few studies on the role of bilingualism in mathematics classrooms explore the intersection of biliteracy, language use, mathematical discourse, and numeracy-especially at the middle school level. Drawing from biliteracy development theory and reform mathematics education literature, this qualitative case study of a dual-language mathematics classroom shows how English language learners (ELLs)/bilinguals use their first (L1) and second language (L2) as resources to access advanced mathematical curriculum. The a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 39 publications
1
11
0
Order By: Relevance
“…In addition to possible increases in learning for ELs taught in their primary language, drawing on a student’s L1 is beneficial because ELs naturally draw on it when engaging in mathematical reasoning (Clarkson, 2007; Rubinstein-Ávila et al, 2015). The process of students’ moving between L1 and L2 is commonly referred to as code switching in the mathematics education literature, although more recently researchers are transitioning to the use of translanguaging (e.g., García & Wei, 2014) in a bid to move away from the deficit framing of much of the early research on code switching (Moschkovich, 2007).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition to possible increases in learning for ELs taught in their primary language, drawing on a student’s L1 is beneficial because ELs naturally draw on it when engaging in mathematical reasoning (Clarkson, 2007; Rubinstein-Ávila et al, 2015). The process of students’ moving between L1 and L2 is commonly referred to as code switching in the mathematics education literature, although more recently researchers are transitioning to the use of translanguaging (e.g., García & Wei, 2014) in a bid to move away from the deficit framing of much of the early research on code switching (Moschkovich, 2007).…”
Section: Resultsmentioning
confidence: 99%
“…Some types of mathematics tasks may create more opportunities than others for ELs to draw on their existing linguistic resources, and teachers of ELs can select such mathematical tasks to facilitate learning opportunities in linguistically diverse classrooms (Barwell, 2005b; Razfar, 2013; Rubinstein-Ávila et al, 2015; Turner & Celedón-Pattichis, 2011). For example, Razfar (2013) examined bilingual Latinx students’ mathematical engagement with open-ended tasks during an after-school program and found that such tasks allowed for students’ use of their L1, which, in turn, helped facilitate students’ meaning making.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A first wave of research in language-as-resource has become a leading trend during the past decade (see, e.g. Barwell, 2009;Bose & Clarkson, 2016;Moschkovich, 2008Moschkovich, , 2015Planas, 2014;Planas & Civil, 2013;Rubinstein-Ávila, Sox, Kaplan, & McGraw, 2015;Setati & Adler, 2000). Recently, researchers in a second wave have problematised (Parra & Trinick, 2018) and theoretically elaborated on (Barwell, 2018;Chronaki & Planas, 2018;Planas, 2018) the language-as-resource metaphor.…”
Section: Introductionmentioning
confidence: 99%
“…While codeswitching implies the recognition of prescriptive language systems and the assumption that communication neatly breaks into languages, translanguaging refers to what people actually do with language to convey meaning. Instead of signaling the alternation of enclosed language systems, translanguaging sees language as an open broader system that allows combinations of social, cultural, and linguistic codes (Rubinstein-Ávila, Sox, Kaplan, & McGraw, 2015). The focus is thus on what learners do by means of all their (social) languages and not on how they perform language in normative ways.…”
Section: Introductionmentioning
confidence: 99%